International Fiesta, Fostering Global Solidarity - Wan Jumani, Fauzi; Lee, Cheng May (Pusat Bahasa Moden (PBM), 2023)
4 November 2023 – The Centre of International Relations (CIR), in collaboration with the Centre for Modern Languages (CML) as well as Confucius Institute (CI) and Centre for Strategic Academic Relations (CSAR), hosted International Fiesta at Astaka Hall, UMPSA Paya Besar Campus.